Improved image processing for 3D virtual object construction from serial sections reveals tissue patterns in root tips of Zea mays - Miki, Yasushi; Saito, Susumu; Niki, Teruo; Gladish, Daniel K. (Applications in plant sciences, 2023)
Premise Previously we described methods for generating three‐dimensional (3D) virtual reconstructions of plant tissues from transverse thin sections. Here, we report the applicability of longitudinal sections and improved image‐processing steps that are simpler to perform and utilize free applications. Methods In order to obtain improved digital images and a virtual 3D object (cuboid), GIMP 2.10 and ImageJ 2.3.0 running on a laptop computer were used. Sectional views of the cuboid and 3D visualization were realized with use of the plug‐ins “Volume Viewer” and “3D Viewer” in ImageJ. Results A 3D object was constructed and sectional views along several cutting planes were generated. The 3D object consisted of selected tissues inside the cuboid that were extracted and visualized from the original section data, and an animated video of the 3D construct was also produced. Discussion Virtual cuboids can be constructed by stacking longitudinal images along the transverse depth direction or stacking transverse images vertically along the organ axis, with both generating similar 3D objects. Which to use depends on the purpose of the investigation: if the vertical cell structures need close examination, the former method may be better, but for more general spatial evaluations or for evaluation of organs over longer tissue distances than can be accommodated with longitudinal sectioning, the latter method should be chosen.